First record of annonaceae wood for the neogene of South America, Amazon Basin, Brazil - Amaral Soares, Emilio Alberto (2016)
The relief of the regions of Manaus and Itacoatiara,Central Amazon, is supported by Neogene siliciclastic rocks, boundedat the base and top by lateritic paleosols and covered by quaternary sedimentarydeposits from the Solimões-Amazon river system. This unitis informally assigned to the Novo Remanso Formation, consists ofusually reddish and ferruginized sandstones, conglomerates and pelites,with few identified fossil records, a fact that has hindered its stratigraphicposition, and the paleoenvironmental reconstruction of the lastphase of the Amazon Basin settling. This study describes, for the firsttime, the occurrence of fossil wood in outcroppings of the left bank ofthe Amazon River, where anatomical and morphological data has enabledits characterization to the species level. Thus, the data marks therecord of the Annonaceae in South America, as well as the depositionalprocesses related to incorporation of organic material in the sandylayer and the fossilization processes that allowed its preservation. In anunprecedented way, this study has described Duguetiaxylon amazonicumnov. gen and sp. and provided information on the anatomical andsystematic character, as well as data on plant-insect interaction, and abetter understanding of the family.